PENGARUH ORIENTASI PASAR, INOVASI PRODUK DAN INKLUSI KEUANGAN TERHADAP KINERJA UKM - Retno Setyowati; Marjam Desma Rahadhini; Aris Eddy Sarwono (Universitas Muhammadiyah Gresik, 2022)
This study aims to analyze the effect of market orientation, product innovation and financial inclusion on the performance of SMEs. This research is a survey research. The population of this research is striated weaving UKM in Mlese Village, Cawas, Klaten. Collecting data using a questionnaire. The sampling technique used the accidental sampling method, namely the striated weaving UKM in Mlese Village, Cawas, Klaten. The sample is 114 respondents. The validity test uses the Pearson correlation product moment, and Cronbach's Alpha for reliability testing. Data analysis used multiple linear regression. The results show that market orientation has a significant effect on the performance of SMEs, product innovation has a significant effect on the performance of SMEs, and financial inclusion has a significant effect on the performance of SMEs. Keywords: financial inclusion; product innovation; SME performance; market orientation